Moduli spaces of compact RCD structures - Navarro, D (2023)
This thesis investigates RCD spaces, which are metric measure spaces with Ricci curvature bounded below and dimension bounded above in a synthetic sense. We introduce moduli spaces of compact RCD structures and study their topology. In particular, we discuss the results obtained in [MN22] (written in collaboration with Andrea Mondino) and [Nav22].